Okoliczności rozpoznania zakażenia HCV wśród osób z przewlekłym wirusowym zapaleniem wątroby typu C = The circumstances of diagnosis of HCV infection among people with chronic hepatitis C - Kowalska, Marta Estera; Kalinowski, Paweł; Bojakowska, Urszula Jolanta (Journal of Education, Health and Sport, 2016)
Kowalska Marta Estera, Kalinowski Paweł, Bojakowska Urszula. Okoliczności rozpoznania zakażenia HCV wśród osób z przewlekłym wirusowym zapaleniem wątroby typu C = The circumstances of diagnosis of HCV infection among people with chronic hepatitis C. Journal of Education, Health and Sport. 2016;6(5):21-28. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.50924 http://ojs.ukw.edu.pl/index.php/johs/article/view/3506 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.04.2016. Revised 25.04.2016. Accepted: 04.05.2016. Okoliczności rozpoznania zakażenia HCV wśród osób z przewlekłym wirusowym zapaleniem wątroby typu C The circumstances of diagnosis of HCV infection among people with chronic hepatitis C Marta Estera Kowalska1, Paweł Kalinowski1, Urszula Bojakowska1,2 1. Samodzielna Pracownia Epidemiologii Uniwersytet Medyczny w Lublinie 2. SKN przy Samodzielnej Pracowni Epidemiologii Uniwersytet Medyczny w Lublinie Słowa kluczowe: wirusowe zapalenie wątroby typu C, profilaktyka Keywords: hepatitis C, prevention Streszczenie Wstęp Wirusowe zapalenie wątroby typu C stanowi jeden z głównych problemów zdrowia publicznego ze względu na długi okres bezobjawowy zakażenia wirusem HCV (hepatitis C virus) oraz brak skutecznej szczepionki. Cel pracy Celem pracy było poznanie i analiza okoliczności rozpoznania zakażenia HCV u osób z przewlekłym wirusowym zapaleniem wątroby typu C, w tym w szczególności sposób/sytuacja wykrycia zakażenia oraz prawdopodobna droga transmisji wirusa. Materiał i metody Materiałem wykorzystanym do badań były odpowiedzi na pytania zamknięte zawarte w autorskim kwestionariuszu ankiety. W badaniu wzięło udział 200 osób z przewlekłym wirusowym zapaleniem wątroby typu C. Wyniki Większość badanych wskazuje kontakt z ochroną zdrowia jako prawdopodobne źródło zakażenia HCV. Osoby badane nie podejrzewały u siebie żadnej choroby wątroby, a wykrycie zakażenia u większości ankietowanych było przypadkowe – podczas wykonywania innych badań lekarskich. Summary Introduction Hepatitis C is a major public health problems due to the long latency period of infection with HCV (hepatitis C virus) and lack of an effective vaccine. Aim The aim of the study was to investigate and analyze the circumstances of the diagnosis of HCV infection in patients with chronic hepatitis C, including in particular the way / situation detection of infection and the likely route of transmission of the virus. Material and methods Material used for the study were answers to closed questions included in the original questionnaire survey. The study involved 200 people with chronic hepatitis C. Results The majority of respondents indicate contact with health as the probable source of HCV infection. Subjects were not suspected at home of any disease of the liver, and the detection of infection in the majority of the respondents was accidental - during other medical tests.